2021
DOI: 10.1080/1343943x.2021.1881409
|View full text |Cite
|
Sign up to set email alerts
|

Modeling biomass and yield production based on nitrogen accumulation in soybean grown in upland fields converted from paddy fields in Japan

Abstract: Crop models can help in identifying constraints to crop production and enhancing crop yield. Because one of the major constraints is the availability of nitrogen for seed production, evaluation of nitrogen accumulation is important for soybean crop models. In the present study, we developed a soybean crop model to evaluate biomass production and nitrogen accumulation of Japanese soybean cultivars grown in upland fields converted from paddy fields. The model simplified the effects of leaf nitrogen deficit on bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Quantitative analysis of biomass accumulation dynamics using model equations is an important method for investigating crop yield formation. Related studies have been reported in crops such as rice (Ji et al, 2012;Li et al, 2010), wheat (Villegas et al, 2001), cotton (Overman & Scholtz, 2013), maize (Meade et al, 2013), and soybean (Nakano et al, 2021;Van Roekel & Purcell, 2014). For example, Wei (Wei et al, 2021) quantitatively analyzed the biomass accumulation dynamics of different rice variety types after transplant based on the Gompertz equation.…”
Section: Introductionmentioning
confidence: 98%
“…Quantitative analysis of biomass accumulation dynamics using model equations is an important method for investigating crop yield formation. Related studies have been reported in crops such as rice (Ji et al, 2012;Li et al, 2010), wheat (Villegas et al, 2001), cotton (Overman & Scholtz, 2013), maize (Meade et al, 2013), and soybean (Nakano et al, 2021;Van Roekel & Purcell, 2014). For example, Wei (Wei et al, 2021) quantitatively analyzed the biomass accumulation dynamics of different rice variety types after transplant based on the Gompertz equation.…”
Section: Introductionmentioning
confidence: 98%